Faktor-faktor yang Berhubungan dengan Perilaku Seks Pranikah pada Remaja - Sifra Maria Pricilia Wahani; Jootje Martin Luther Umboh; Lydia Tendean (Indonesian Journal of Public Health and Community Medicine, 2021)
Background: Premarital sexual behavior in adolescents is currently in a frightening stage where more and more teenagers have had sex. There are several factors related to this behavior such as knowledge, information media, religiosity and family roles. The purpose of this study was to analyze the factors related to premarital sexual behavior in adolescents at the State Vocational High School (SMKN) 2 Tondano. Method: This is an observational research with a cross sectional study approach. This research was conducted at SMKN 2 Tondano in April-May 2018. The subjects in this study were 74 students aged 16-18 years. Samples were taken using a simple random sampling. The variables studied in this study were premarital sex behavior as the dependent variable. Knowledge, sources of information, religiosity and family roles as independent variables. Data obtained through interviews. The measuring instrument used is a questionnaire. Data analysis was carried out univariate and bivariate. Results: The results showed that the most distributed respondents were in poor knowledge (55.4%), good sources of information (58.1%), good religiosity (56.8%), good family roles (55.4%) ) and unfavorable premarital sex behavior (63.5%). The results of the bivariate analysis showed that knowledge, sources of information and family roles were related to premarital sex behavior in adolescents while religiosity was not related. Conclusion: The conclusion of this study is that knowledge, sources of information and family roles are factors related to premarital sex behavior in adolescents at SMKN 2 Tondano. Therefore, there is a need for programs that can increase knowledge such as counseling, disseminating correct sex information and increasing parental supervision of teenagers.